STRATEGI DAN PERAN HUMAS DALAM MENINGKATKAN KETERBUKAAN PELAYANAN INFORMASI PUBLIK DI SEKERTARIAT DAERAH KOTA PANGKAL PINANG - Wati, Eka Kusuma; Hidayat, Wahyu; Rizaldi, Rizaldi (Universitas Panca Marga, 2023)
The purpose of this research is to know the Effect of Service Quality of PatientSatisfaction At The Regional General Hospital (RSUD) dr. Mohamad Saleh City of Probolinggo. The study type utilized in this article is a quantitative approach, which tries to test hypotheses about the cause-and-effect relationships between the variables researched. A quantitative method is one that explains or describes something. In contrast, the quantitative method uses a survey approach for data collection. The survey is a quantitative study that is the same for many people. And then, the researcher records, processes, and analyzes all of the answers they get. A total of 100 patients were taken as samples for this study, and data collection was carried out using a questionnaire using the Likert scale given to patient respondents. The results of the analysis of this study can be shown that based on the results of the regression of service quality (X) of 33.037, it indicates It demonstrates that independent variables have no effect whatsoever on the evaluation findings for service quality. However, the Service Quality (Y) regression result of 0.362 shows a positive contribution made by Service Quality, indicating that a 1 point improvement in Service Quality will have a 0.362 point impact on Service Quality. In other words, the patient's pleasure rises as service quality improves.